KOORDINASI PENANGGULANGAN ACQUIRED IMMUNE DEFICIENCY SYNDROME (AIDS) DI KOTA PEKANBARU - Nurrahmad Pebriansyah; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
AIDS Commission as the implementer of AIDS prevention coordination based on Pekanbaru Mayor Regulation No. 32 of 2013 on Prevention and Response of HIV and AIDS in Pekanbaru City. In coordinating the implementation of AIDS prevention, the symptoms of lack of participation of leaders between the AIDS Prevention Committee and other institutions in Pekanbaru City either formally or through coordination meetings and the delegation of authority in the implementation of coordination. Based on these matters, the researcher wishes to conduct qualitative descriptive research about how the implementation of AIDS prevention coordination and the factors that hinder the coordination of AIDS prevention in Pekanbaru City. This study aims to find out and analyze the coordination of AIDS prevention and to know and analyze the factors that hinder the coordination of AIDS prevention in Pekabaru City. This study uses theoretical concepts according to Hasibuan (2011) about coordination tools that use 4 ways: Division of Tasks, Discipline, Meeting, and Unity of Action. Then for the factors that hamper based on the author's observation in lapngan that is less supportive facilities and infrastructure, insufficient budget, poor community participation, and the participation of the coordinating leaders of the institution which is an obstacle in coordinating AIDS management in Pekanbaru City so that the optimal response has not yet been manifested.Keywords: Coordination, AIDS Prevention